Alaskan malamutes : everything about purchase, care, nutrition, behavior, and training - Siino, Betsy Sikora (Hauppauge, NY : Barron's, 2008)
A guide to keeping Alaskan malamutes as pets, reviewing the history of the breed, discussing housing needs, feeding, grooming, health care, and activities, and offering advice on choosing an Alaskan malamute.
Includes bibliographical references (p. 92-93) and index.
Adult
Keywords: Alaskan Malamute; Alaskan Malamutes